Structure and function of a β-1,2-galactosidase from Bacteroides xylanisolvens, an intestinal bacterium - Yutaka Nakazawa; Masumi Kageyama; Tomohiko Matsuzawa; Ziqin Liang; Kaito Kobayashi; Hisaka Shimizu; Kazuki Maeda; Miho Masuhiro; Sei Motouchi; Saika Kumano; Nobukiyo Tanaka; Kouji Kuramochi; et al. (Communications Biology)
Abstract Galactosides are major carbohydrates that are found in plant cell walls and various prebiotic oligosaccharides. Studying the detailed biochemical functions of β-galactosidases in degrading these carbohydrates is important. In particular, identifying β-galactosidases with new substrate specificities could help in the production of potentially beneficial oligosaccharides. In this study, we identify a β-galactosidase with novel substrate specificity from Bacteroides xylanisolvens, an intestinal bacterium. The enzyme do not show hydrolytic activity toward natural β-galactosides during the first screening. However, when α-d-galactosyl fluoride (α-GalF) as a donor substrate and galactose or d-fucose as an acceptor substrate are incubated with a nucleophile mutant, reaction products are detected. The galactobiose produced from the α-GalF and galactose is identified as β-1,2-galactobiose using NMR. Kinetic analysis reveals that this enzyme effectively hydrolyzes β-1,2-galactobiose and β-1,2-galactotriose. In the complex structure with methyl β-galactopyranose as a ligand, the ligand is only located at subsite +1. The 2-hydroxy group and the anomeric methyl group of methyl β-galactopyranose faces in the direction of subsite −1 and the solvent, respectively. This observation is consistent with the substrate specificity of the enzyme regarding linkage position and chain length. Overall, we conclude that the enzyme is a β-galactosidase acting on β-1,2-galactooligosaccharides.